ANALISIS NILAI EKONOMI OBJEK WISATA AIR TERJUN TANJUNG BELIT DI KECAMATAN KAMPAR KIRI HULU KABUPATEN KAMPAR DENGAN PENDEKATAN METODE BIAYA PERJALANAN - Oktaviani Fuji Lestari; Syapsan '; Ando Fahda Aulia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This reseach was conducted in Tanjung Belit waterfall located in Kampar Kiri Hulu area Kampar Regency. The aim of this research is to know the economic value of Tanjung Belit waterfall and to examine the effect of travelling cost, income and house distance on the number in visitor of Tanjung Belit Waterfall. The population of this research was the visitor who visited the waterfall in the last recent years coming to the Tanjung Belit waterfall on 2015 was as 6289 people. Accidental sampling is used in this research, means that whoever accidentally met while the writer collecting the data there. There were 44 people as the sample get.The method of this research is using descriptive and quantitave data collection. Quantitative analysis is using multiple linear regression which was based on questionare. Using traveling cost approach, it can be shown that the economic value of the Tanjung Belit Waterfall is Rp670.532.706,72,-. Using the multiple regresion method, distance significanty affects numbers of visitor to Tanjung Belit Waterfall. While by using F-test shows that the travelling cost, income and house distance is havea significant effect to the visitors who visit the waterfall. Manager should increase the environment quality, the beauty and to be more aware to the visitor and also increasing the all needs of the visitor during the visited time to increase the economic value of Tanjung Belit Waterfall.Keywords :Waterfall Tanjung Belit,economic value, and travel cost method.